Exploring challenges to implementing an effective agriculture-based TVET program in South Africa - Ramongwane, Daniel; Ramaligela Sylvia Manto; Makgato Moses (Journal of Technical Education and Training, 2022)
Abstract: Technical and Vocational Education and Training (TVET) is an educational field that emphasises on practical and lab-based learning environments. Equally important, TVET also makes a major contribution to the agriculture field. However, there are myriad issues that cause limited knowledge and skills for agricultural graduates, and these include but are not limited to the lack of resources, equipment, and infrastructure. The case study approach allows the in-depth collection of data through interviews and the observation of complex issues in their real-life settings. The research participants were purposefully and conveniently sampled due to their experience in agricultural programmes. The findings were presented using thematic analysis based on Mitzel’s model which covers practical knowledge and skills, teaching skills, teaching styles, and personality traits. According to the study’s findings, the lack of resources, equipment, and infrastructure restricted a lecturer’s capacity to release their practical knowledge and skills, their teaching skills, teaching styles, and their personality factors when teaching agricultural programmes. The recommendation advises allocating the TVET colleges with adequate resources, equipment, and infrastructure to facilitate agricultural knowledge and skills.